Nilai-Nilai Karakter pada Anak Dalam Permainan Tradisionan dan Moderen - Irman, Irman (Universitas Islam Negeri Raden Intan Lampung, 2017)
Play has character values for the child's life. Specifically the game can be divided into two, namely the traditional game performed by children who live in the countryside and modern games performed by children who live in urban areas.To dig the character values on the game the researchers used a qualitative approach. The results of the study found, (1) Traditional games generally use natural game tools and games where the game is done in the open, while modern games use electronic devices, and are generally performed in enclosed spaces, (2) traditional games and modern games have value character values on the cognitive, social, emotional and identity aspects, and (3) traditional games highlight the values of social character, while modern games highlight the values of individual characters. The results can be used by educators, especially school counselors to make the game as a technique in counseling in shaping the character of students.